The words of prevention, part I: changing the model - Marc Jamoulle; Enrique Gavilán; Raquel Vaz Cardoso; María Ana Mariño; Miguel Pizzanelli (Sociedade Brasileira de Medicina de Família e Comunidade, 2015)
Objective: this part I article explores the different meanings of relevant keywords for General Practice/Family Medicine (GP/FM) in the prevention domain. The aim is to contribute to information process in GP/FM by keeping in line with the main terms used in health care organization. Methods: important keywords for GP/FM in the prevention domain were selected. Then, a search was carried out on the main sources in GP/FM databases, as well as in Medical Subject Heading and major terminological databases available online. Results and Discussion: there is discrepancy between the conceptual contents of major prevention models amongst the usual bibliographic sources of knowledge in GP/FM in particular and medicine in general. Conclusion: For GP/FM, distribution of preventive activities is now firmly established on a new constructivist model, privileging the doctor-patient relationships and introducing a cybernetic thinking on the health care activities with a special commitment to ethics and the positive duty of beneficence.